Toughening of Epoxy Resin via Silane Terminated Urethane Including Pre-Hydrolyzed Tetraethoxysilane - KARTAL, İLYAS (ASIAN JOURNAL OF CHEMISTRY, 2014)
In this Study, firstly; Silane terminated urethane was synthesized from poly(hexamethylene carbonate) diol and 3-isocyanatopropyl trimethoXysilane. Prepared solutions of inorganic part (silane terminated urethane + pre-hYdrolyzed tetraethoxysildne) were Mixed with epoxy-hardenet mixture to obtain hybrid solutions. Various hybrid Solutions were prepareclnsing different epoxy/inorganic part solution:compositions. Furthermore, ther'effect of silane terminated urethane on the mechanical and morphological properties of epoxy was investigated. The structure and pioperties of the composites are characterized using a scanning:electron Microscopy. Epoxy/silane, terminated I urethane hybrid materials were Subjected to examinations to obtain their tensile strength, three point bending properties, hardness, izod impact strength. Incorporation of silane terminated urethane into the epoxy resin greatly Modified the impact behavior of hybrids.
Keywords: Polyurethane; Epoxy resin; Hybrid polymer; INTERPENETRATING POLYMER NETWORKS; LIQUID RUBBERS; FRACTURE; COMPOSITES; MECHANISMS